Entry Regulation and Formalization of Microenterprises in Developing Countries - Bruhn, Miriam; McKenzie, David (World Bank, Washington, DC, 2013)
The majority of microenterprises in most developing countries remain informal despite more than a decade of reforms aimed at making it easier and cheaper for them to formalize. This paper summarizes the evidence on the effects of entry reforms and related policy actions to promote firm formalization. Most of these policies result only in a modest increase in the number of formal firms, if at all. Less is known about the impact of other forms of business regulations on the performance of low-scale enterprises. Most informal firms appear not to benefit on net from formalizing, so ease of formalization alone will not lead to most of them formalizing. Increased enforcement of rules can increase formality. Although there is a fiscal benefit of doing this with larger informal firms, it is unclear whether there is a public rationale for trying to formalize subsistence enterprises.